Etiquette in an Organization Life, the Most One But Not Really Done Yet - Sri Wibowo, Bambang (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2022)
The globe is changing everytime beyond our logic everywhere without alarming sometimes. Eastern and western culture being mixed everywhere, since the electronic era had been upgraded here and there without questions. Organization culture is changing too in many ways due to the culture shock of the employees, so that human resource with etiquette will be a unique one to be found. Etiquette could drag the organizational behavior to be a better circumtance for everyone and clients too, because this behavior would bring the air of comfortness for internal and external working process. Organization’s staffs with etiquette will be a high priced treasures of organizational behavior for the organization itself, because no more wonder they could build a comfortable atmosphere for everyone who worked for the organization. Etiquette will bring all the staffs of an organization into a comfortable and suitable atmosphere for internal ( teamwork and individual work ) or external connectivity, so that the process of reaching the organization’s goals will be easier. A comfortable air will set everyone’s mind on the right path as it should be to guide them to be someone with a plus poin personality which is needed by his or her surrounding. In order to set a comfortable air for a healthy organization modern life, the organization’s management should think about empowering its human resource, specially personality and psychology empowerment for their own good future and their own good brand, as we all knew that a brand can bring an organization to the top or the lowest poin of its level